The Relationship between Educational Level and the Role of Parents with Learning Achievement in Mathematics - Mardiati, Diah Chairi; Alorgbey, Bernard; Zarogi, Abubakar Bawa (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the relationship between parental education level and student learning achievement and between the role of parents and student learning achievement which was carried out at State Elementary Islamic School 1 South Tangerang. Methodology: This research uses a correlational quantitative approach. The sample to be studied is 36 students. The sample used in this research, the author used a Nonprobabillity Sampling technique, Saturated Sampling/Census type. this research uses data collection methods in the form of documentation and distributing questionnaires. The data analysis techniques used in this research are descriptive analysis and parametric statistical analysis. Main Findings: The results of this study show that there is a positive and significant relationship between the level of parental education and the learning achievement of class V Madrasah Ibtidaiyah Negeri 1 South Tangerang City students with a correlation coefficient of 0.357. And there is also a significant positive relationship between the role of parents and the learning achievement of class V Madrasah Ibtidaiyah Negeri 1 South Tangerang City students with a correlation coefficient value of 0.359 Novelty/Originality of this study: This study provides a new perspective that the combination of parents' high level of education and their active involvement in their children's education is a stronger determining factor in improving mathematics achievement than other factors.